The Hoax of SARA (Tribe, Religion, Race, and Intergroup) as a Threat to the Ideology of Pancasila Resilience - Kuntarto, Kuntarto; Widyaningsih, Rindha; Chamadi, Muhamad Riza (SCAD Independent, 2021)
The subject of this research is to provide an overview of the mechanisms and schemes of hoax news spreading. Research is also trying to provide an explanation threat of hoaxes about SARA (Tribe, Religion, Race, and Intergroup) towards the resilience of the Pancasila ideology. The method used in this research is a descriptive qualitative method by describing the results of the 2019 Mastel survey of national hoax outbreaks using the Pancasila ideology approach as a perspective of the study. The results showed that the hoax on the issue of SARA was the second most widely hoax news content received by the public with the popular channels for hoax distribution is social media, with a kind of text messaging. A hoax about SARA is the most frequently accepted hoaxes in the community every day. The scheme of spreading hoax news is by spreading slander to political opponents, excessive branding of leader/figure, fake testimony, irresponsible quotation, and bombastic photos or titles. Hoax news about SARA issues poses a severe threat to Indonesia's unity because triggering controversy, public unrest, sectarian sentiment, intolerance of political instability, and security disturbances.